(untitled) (Bangladesh Journal of Animal Science, 2017)
The aim of this paper is to review the current status of quail production, problems and its future prospects in Bangladesh. Poultry industry is an important sub-sector of livestock production in Bangladesh that plays a crucial role in economic growth and simultaneously creates numerous employment opportunities. As a fundamental part of animal production in Bangladesh, the industry is committed to supplying nation with a cheap source of good quality nutritious animal protein in terms of meat and eggs. Approximately 25% of the protein consumed in Bangladesh originates from poultry .Despite this data, Bangladesh is still one of the lowest poultry meat consuming countries in the world. Here per capita meat consumption is only 1.2 kg per person per year and per capita egg consumption is also about 32 eggs per person per year. With increasing incomes, the demand for meat, especially the cheaper option of poultry meat, and eggs is set to rise. More importantly, quail becomes a promising poultry species in Bangladesh due to their smaller body size, hardiness against common chicken diseases, easy management, quick return over the invest, less labor cost and investment required for the farming. But still now the rearing quail is not yet popular like chicken farming due to poor marketing channel, subsistence farming, lack of specialized feed, lack of available day-old chicks, high chick mortality etc. Scientific feeding, training to the farmers about their management, creating organized marketing channel will be the probable solution for vitalizing this species in Bangladesh. Bang. J. Anim. Sci. 2017. 46 (2): 109-120